Design of a morphing airfoil - Varsha Ravichandran (2013)
In this continued study, macro fibre composite actuators are used to change the upper and lower surfaces of the air-foil model with a geometry closely resembling NACA0014. These thin and light piezoelectric actuators are bonded to the inside skin of the upper and lower surfaces and become an integral part of it. In order to assess its characteristics of the static and dynamic changes of the airfoil, it is tested in still air and wind tunnel measurements in flow regimes of Reynolds number 150,000. The results obtained can be used to design a wing with morphing surfaces for improving its aerodynamics, for manoeuvring without ailerons, and/or for active control of the flow over the wing.